2019
DOI: 10.1152/japplphysiol.00811.2018
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent skeletal muscle transcriptome response to bed rest-induced atrophy

Abstract: Short-term muscle disuse induces significant muscle loss in older adults and in some reports may be more accelerated with aging. Identifying muscle transcriptional events in response to bed rest may help identify therapeutic targets to offset muscle loss. Therefore, we compared the muscle transcriptome between young and older adults after bed rest and identified candidate targets related to changes in muscle loss. RNA was sequenced (HiSeq, Illumina; DESeq, R) from muscle biopsies obtained from young [ n = 9; 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 40 publications
(63 reference statements)
5
40
1
Order By: Relevance
“…The current data show that the biological perturbations in skeletal muscle after 84 days of bed rest are at least as large, if not greater, than what has been described after 21 15 or 60 days of bed rest 18,19 . For example, pathways related to mitochondria, energy metabolism, and structural components were downregulated, and those involved in the ubiquitin system upregulated, which is consistent with findings in skeletal muscle after short‐ 10‐15,17 and moderately long periods of unloading 18,19 . Similarly, we found a transcriptomic profile indicating slow‐to‐fast fiber transition, a common event in unloading studies 6,43‐46 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The current data show that the biological perturbations in skeletal muscle after 84 days of bed rest are at least as large, if not greater, than what has been described after 21 15 or 60 days of bed rest 18,19 . For example, pathways related to mitochondria, energy metabolism, and structural components were downregulated, and those involved in the ubiquitin system upregulated, which is consistent with findings in skeletal muscle after short‐ 10‐15,17 and moderately long periods of unloading 18,19 . Similarly, we found a transcriptomic profile indicating slow‐to‐fast fiber transition, a common event in unloading studies 6,43‐46 .…”
Section: Discussionsupporting
confidence: 90%
“…Hitherto attempts to provide mechanistic information on the molecular programs governing unloading‐induced muscle deconditioning have included the exploration of transcriptome changes in muscle after short‐term bed rest or unilateral lower limb suspension/cast immobilization, ranging from 24 hours to 21 days, 10‐17 or longer periods of bed rest (60 days) 18,19 . A common disuse signature, regardless of the differences in methods and/or study duration, is a marked downregulation of gene networks related to both energy metabolism and structural components, together with an upregulation of the ubiquitin‐proteasome pathway 10‐12,14,15,17‐19 .…”
Section: Introductionmentioning
confidence: 99%
“…Costameres assembly is jeopardized by unloading, because of either decreased FAK activation or reduced expression of the kinase and its inhibitor FRNK, which characterized human muscle already after 8 day bed rest . Five days of bed rest are sufficient to downregulate transcriptome of integrin signalling pathway in both young and old subjects . Our finding that melusin, a FAK‐interacting protein, decreased early after unloading also in human muscle is in line with these reports and may represent a major determinant of costamere deregulation.…”
Section: Discussionsupporting
confidence: 88%
“…Lastly, we found the extracellular matrix and collagen pathways to be significantly up-regulated in the CON group with BR, which was attenuated in the HMB group. A recent investigation also found fibrotic pathways to be significantly up-regulated in older adults after 5 days of BR ( 31 ). Up-regulation of the extracellular matrix and collagen proteins may have important implications for skeletal muscle function.…”
Section: Discussionmentioning
confidence: 88%
“…These findings are supported by our recent findings in a preclinical animal model of disuse atrophy in which several upstream regulators, for example, PGC-1α and ERRα, of mitochondrial biogenesis and energetics were significantly affected ( 30 ). Mahmassani et al also found mitochondrial dysfunction and oxidative phosphorylation pathways were significantly regulated in both young and old individuals following 5 days of BR ( 31 ). Collectively, these studies highlight the potent effect of short-term disuse on skeletal muscle oxidative metabolism and mitochondrial transcriptome.…”
Section: Discussionmentioning
confidence: 97%